Seasonal siitfting and its impact on crop production: local community perception of Satkhira district - Nipa, Sharmin Nahar; Mukherjee, Nandan; Khan, Md. Reaz Uddin; Akhter, Taslima; Khanum, Roufa; Khan, A S Moniruzzman; Nishat, Ainun (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].